DEVELOPMENT OF A PLANT TISSUE CULTURE TEXTBOOK BASED ON PROJECT-BASED LEARNING TO ENHANCE THE SCIENCE PROCESS SKILLS OF BIOLOGY STUDENTS - Monica Septiani Br Mangunsong; Fauziyah Harahap; Nurul Huda Panggabean; Aristo Hadinata; Cicik Suriani; Syahmi Edi (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to determine the feasibility of a Project-Based Learning (PjBL)-based Plant Tissue Culture textbook in improving the science process skills of biology students at Universitas Negeri Medan, based on evaluations from material experts and media experts. It also aims to identify the responses of lecturers and students toward the developed textbook and to assess its effectiveness in enhancing students’ science process skills in plant tissue culture material at Universitas Negeri Medan. The study was conducted from August to November 2024 in the Department of Biology, Universitas Negeri Medan. The research employed the 4D development model, which includes the stages of define, design, develop, and disseminate. To measure the effectiveness of the developed textbook on students’ science process skills, the N-Gain test was used. The results showed that the feasibility of the PjBL-based plant tissue culture textbook in improving biology students’ science process skills, based on the assessment of material experts, obtained an average score of 76.66% (feasible), while the media experts gave an average score of 94.04% (highly feasible). The lecturers’ response reached an average percentage of 95% (highly feasible). The students’ responses were also very positive: the individual trial obtained 94.16%, the small group trial obtained 91.75%, and the large group trial obtained 90.92%, all categorized as highly feasible. Based on the N-Gain test results, the developed PjBL-based plant tissue culture textbook was found to be quite effective in improving the science process skills of biology students at Universitas Negeri Medan.